Role of intermittent hypoxic expression of Hypoxia Inducible Factors and NFKB in endurance exercise - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Uday Younis, Hussein (2014)
We have read the respective article and we agreed with all great findings. Nevertheless, we wish to emphasize the need to address the role of some molecular and physiological markers that may elaborate and possibly support the findings of the study. Intermittent hypoxia exposure can enhance the generation of red blood cells, which may consequentially increase hemoglobin concentration and hematocrit depending on the model of IHE exposure and its effect on serum hypoxia inducible factors (HIF-1 alpha, HIF-2alpha and HIF-3 alpha), erythropointin (EPO) levels and some signaling pathways (such as those mediated by the nuclear factor-kappa light chain B: NF-kB for stress and inflammation examinations)